PENGARUH GENDER, COMMITMENT, COMMUNICATION, DAN CONFLICT HANDLING TERHADAP CUSTOMER LOYALTY PADA SALAH SATU BANK SWASTA DI INDONESIA - Setiawan Jatmiko (Jurnal Manajemen dan Pemasaran Jasa, 2011)
The background of this research is how to winning the competitions in banking industry sector, build a relationship and make customers to be loyal, to makes banking managers must strive to develop their strategy to achieve customer loyalty. The objectives of this research is to investigate the effect of gender, commitment, communication and conflict handling on customer loyalty in Indonesian private banking. A theoritical framework was developed to test the effect among the study construct. The design of this research applies to one of the biggest local bank in Indonesia and the questionares were spreaded away to 150 respondents / customers from 4 branches in Jakarta and by using purposive sampling. The results of this research show that gender does not significantly effect on customer loyalty but commitment, communication and conflict handling are significantly effect on customer loyalty.Keyword : gender, commitment, communication, conflict handling and customerloyalty